'We have no crystal ball' - advance care planning at nursing homes from the perspective of nurses and physicians. (3rd April 2019) - Kastbom, Lisa; Milberg, Anna; Karlsson, Marit
Abstract: Objective: To investigate clinicians' perspectives on the factors that shape the process of advance care planning in a nursing home context. Design: Interviews. Latent qualitative content analysis. Setting: Nine nursing homes in Sweden. Subjects: 14 physicians and 11 nurses working at nursing homes. Main outcome measures: Participants' views on advance care planning (ACP) at nursing homes. Results: The analysis of the interviews resulted in four manifest categories: Exploration of preferences and views, e.g. exploring patient wishes regarding end-of-life issues and restrictions in care at an early stage, and sensitivity to patient's readiness to discuss end-of-life issues; Integration of preferences and views, e.g. integration of patient's preferences and staff's and family member's views; Decision & documentation of the ACP, e.g. clear documentation in patient's medical records that are up-to-date and available for staff caring for the patient, and Implementation & re-evaluation of the ACP, e.g. nurse following up after ACP-appointment to confirm the content of the documented ACP. The latent theme, Establishing beneficence – defending oneself against tacit accusations of maleficence, emerged as a deeper meaning of all the four (manifest) parts of the ACP-process Conclusion: This study stresses the importance of involving patients, family members, and the team in the work with advance care planning in nursing homes. In addition, clear medical record documentation and proficiency in end-of-life communication related to advance care planning for physicians as well as nurses may also be factors that significantly shape advance care planning in a nursing home context. Key Points: Advance care planning can help patients to receive care in line with their preferences and can positively impact quality of end-of-life care. Our results describe a process consisting of four manifest categories and one latent theme constituting the process of advance care planning, that may be considered in education in advance care planning. The significance of nurses and physicians perceiving beneficence as well as fear of accusations of maleficence are important factors to contemplate. The study has implications for healthcare staff caring for patients near the end of their lives, in particular patients in nursing homes.